Seasonal incidence, population dynamics and morphometric traits of exotic coconut whiteflies in southern Tamil Nadu - S Suriya; G Preetha; N Balakrishnan; J Sheela (Journal of Horticultural Sciences, 2023)
Survey was conducted at fortnightly intervals to assess the intensity of damage caused by the invasive whiteflies in coconut in the southern districts of Tamil Nadu viz., Thoothukudi, Tirunelveli, Tenkasi and Kanyakumari from December 2020 to August 2021. Among the four districts, Kanyakumari recorded the highest whitefly incidence (56.30%), whereas, Tenkasi showed the lowest infestation (48.83%). Two whitefly species viz., rugose spiralling whitefly, Aleurodicus rugioperculatus Martin and bondars nesting whitefly (BNW), Paraleyrodes bondari Peracchi were observed in all the surveyed districts. The rugose spiralling whitefly nymphs and adult populations were found to be highest in Kanyakumari (49.46 nymphs/leaflet; 36.99 adults/leaflet) and lowest in Tenkasi (32.76 nymphs/leaflet; 26.71 adults/leaflet). Similarly, the population of bondars nesting whitefly nymphs and adults were highest in Kanyakumari (35.31 nymphs/leaflet; 34.84 adults/leaflet), whereas, the lowest nymphal population was observed in Tenkasi (22.79 nymphs/leaflet) and adult population in Thoothukudi (24.19 adults/leaflet). In morphometric analysis, length and breadth of egg (0.24 ± 0.03 mm and 0.13± 0.02 mm), nymphal (0.83 ± 0.08 mm and 0.38 ± 0.04 mm), pupal (1.08 ± 0.09 mm and 0.70 ± 0.09 mm), adult (female: 2.59 ± 0.09mm, 1.71 ± 0.14 mm; male: 2.27 ± 0.21 mm, 1.30 ± 0.05 mm) was recorded for A. rugioperculatus and egg (0.15 ± 0.02 mm and 0.08 ± 0.01 mm), nymphal (0.46 ± 0.02 mm and 0.36 ± 0.02 mm), pupal (0.59 ± 0.16 mm and 0.41 ± 0.09 mm), adult (1.09 ± 0.08 mm and 0.73 ± 0.07 mm) for P. bondari.